Strategi Komunikasi Dalam Advokasi Kebijakan Pengendalian Tembakau (Studi Kasus Lentera Anak): Communication Strategies in Tobacco Control Policy Advocacy (Case Study: Lentera Anak) - Wahyudi, Anatasia; Vania, Olvi; Dennysal, Selena; Derlin, Diane; Risky, Qonitha (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Tobacco control in Indonesia faces multidimensional challenges, primarily driven by the high prevalence of smokers among children and adolescents, weak regulatory frameworks for health protection, and aggressive interference from the tobacco industry. The industry systematically manipulates public narratives, linking tobacco consumption to state revenue and the welfare of tobacco farmers to hinder stricter regulations. In this context, the Lentera Anak Foundation, a civil society organization focused on child protection, has positioned itself as a leading advocate in promoting stronger and more comprehensive tobacco control policies. This research employs a qualitative case study method to analyze the communication strategies utilized by Lentera Anak in advocating for the revision of Government Regulation Number 109 of 2012. The primary objective is to examine the strategic communication methods employed, such as public campaigns, high-level advocacy targeting policymakers, social media utilization, and grassroots mobilization. Furthermore, the study identifies supporting and hindering factors, particularly industry lobbying and public apathy, while evaluating the effectiveness of these strategies in influencing public policy and protecting children from tobacco exposure. The findings highlight the critical importance of interpersonal and community-based communication, the construction of strong counter-narratives to challenge industry propaganda, and multi-stakeholder engagement, including active youth participation and collaboration with relevant ministries. The study concludes that a consistent, evidence-based, and inclusive communication strategy is essential to maintaining public awareness, advancing policy reform, and ensuring the long-term protection of children from the pervasive influence of the tobacco industry in Indonesia.